Medieval military architecture in the Royal Cistercian Abbey of Santa Maria de Piedra: Malavella Castle, the gate-tower and the wall - González Zymla, Herbert (Anales de Historia del Arte, 2011)
The Royal Cistercian Monastery of Santa María de Piedra (Saint Mary of Stone) was founded in 1195. It displays remarkable medieval vestiges some of which must be studied within military architecture. By combining the employment of documents and material rests it can be recognised four construction stages. The first one is Malavella Castle, previous to the foundation of the abbey and a notable work of the military architecture of the mid of the 12th century. The king Alfonso II (Alphonsus II) donated it to the monks so that they could use the castle as the starting point to build the abbey. Of Malavella Castle there are evidences of having counted both on a hardly recognizable gate tower at the level of the mandatum and rests with a barrel vault in the cella and the passage of the convert. The second stage is contemporary to the foundation of the abbey and must be dated the first third of the 13th century. To this second stage must correspond the design of the external fortified enclosure and the monumental gate tower. The wall and the towers keep a fully military and strategic use. The third stage matches the beginning of the 15th century and it is the adaptation of the gate tower to diverse liturgical uses on being added an expository balcony to exhibit the Sacro Dubio of Cimballa, the most outstanding relic that the monastery owned in the Middle Ages. The fourth stage is the consolidation and reconstruction of the walled fence in the first third of the 17th century, age when the fabric banners were substituted by the emblems and coat of arms carved in stone, assuming a series of political values and new symbols.